Stormwater Detention Structures in the Veranda and Parking Lot at Commercial Centre Subjected to Historical Extreme Rainfall Events - Mah, Yau Seng; Merry Tang, Shi Ting; Teo, Fang Yenn (Construction Research Institute of Malaysia (CREAM), 2023)
This paper reports on a specifically designed stormwater detention structures that fit in a commercial centre, namely modular-based water micro tanks in the veranda and the parking lot in front of shop buildings. This is in line with the concept of integrating detention structures into urban features as small pockets to capture urban runoff along the stormwater flow path so that the amount of stormwater flowing downstream is reduced. The two designs were simulated using Storm Water Management Model and subjected to historical rainfall data, in which the selected storms were found to span more than 10 hours and with maximum hourly rainfall depths between 40 - 70 mm. Results from the modelling efforts were stormwater characteristics of the particular type of detention system in times of extreme rainfall events. The identified stormwater characteristics provide a guide to urban planners to mitigate urban flooding. It was found that the detention structures, although with a limited storage volume, were able to sustain an accumulated rainfall up to 60 mm, a feature 3 times higher than the 23 mm design rainfall. It was found that accumulated rainfall of a particular storm was a better indicator than the maximum rainfall depth of the storm to indicate the water storing capacity of detention structures.